Neocolonialism in the globalised economy of the 21st century: An overview - Ziai, Aram (Momentum Quarterly, 2020)
Starting from Kwame Nkrumah’s definition of neocolonialism, this article examines practices in the globalised economy in the areas of debt, structural adjustment, development cooperation and agricultural policy, as well as the major institutions of the global political economy (World Bank, IMF, WTO). The article concludes that neocolonialism and the control of the economy through foreign actors is a regular feature of today’s economy. Yet these actors are not necessarily always identical to former colonial powers.